VACTERL Association Complicated with Right-sided Congenital Diaphragmatic Hernia - Ray Hung Chen; Han-Yang Hung; Nien-Lu Wang; Shin-Lin Shih; Haw-Kwei Hwang; Tung-Yao Chang; Paul H. Chen; Jui-Hsing Chang (Pediatrics and Neonatology)
We describe a neonate with VACTERL association and right-sided congenital diaphragmatic hernia (CDH). Such coexistence is rare. The lack of symptoms during the early neonatal period, the absence of bowel loops herniated into the right thoracic cavity, and an unfinished surgery led to clinical and radiological diagnostic difficulties. Respiratory distress occurred when the patient was 2 months old. Chest radiology plain film revealed typical findings of right-sided CDH. The diagnosis was confirmed after surgical exploration.